Amendment of the Corruption Eradication Commission Act and Its Impact on the Constitution - Josef Mario Monteiro (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2021)
This study analyzed the sub-system factors influencing the amendment of the Corruption Eradication Commission Act (KPK Law) from the Cybernetics theory and the impacts on the Constitution. According to this theory, there are various kinds of sub-systems, where one sub-system is interrelated with other sub-systems. Each of the sub-systems referred to will influence each other based on the primary function of each of these sub-systems, such as the cultural sub-system, which has the primary function of maintaining patterns, the social sub-system as a function of integrity, the political function as a function of achieving goals, and the economic sub-system as an adaptive function. This doctrinal legal research employed statutory approaches and concepts and found that changes in the KPK Law are influenced by the political sub-system factor, particularly the strong political interests of the House of Representatives and the Government. As a result, the amendment to the KPK Law is undemocratic because it does not fulfill the formal and material principles. In addition, it does not philosophically fulfill the function of law, leading to constitutional values violation.